SINTESIS DAN KARAKTERISASI SENYAWA ION BARIUM SULFAT (BaSO4) - Iis Siti Jahro; Amanda Riani Hutagalung; Nazwa Syahwana; Efrida Handayani Marpaung; Riyanda Syahfitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to synthesize and characterize barium sulfate (BaSO?) as an ionic compound using a precipitation method, as well as to analyze its physical properties and solubility based on laboratory experimental results. The synthesis was carried out by reacting barium chloride (BaCl?) and sodium sulfate (Na?SO?) solutions in an aqueous medium, resulting in the formation of a white BaSO? precipitate. The precipitate was then separated through filtration, washed with distilled water, and dried to obtain a stable solid product. Characterization was conducted through physical and solubility tests. The results showed that the obtained BaSO? was in the form of a fine white powder. In the solubility test, the compound was found to be insoluble in water, indicating that BaSO? has very low solubility. Based on stoichiometric calculations, the theoretical mass was 2.33 grams, while the experimental mass was 0.55 grams, resulting in a percentage yield of 23.6%. The relatively low yield indicates that the synthesis process was not fully optimal. Theoretically, the formation of BaSO? precipitate is influenced by its very low solubility product constant (Ksp), causing Ba²? and SO?²? ions in solution to form a solid phase. The results of this study are consistent with theoretical principles in terms of precipitate formation, physical properties, and solubility, although differences were observed in the quantitative results. Keywords: Baso?, Precipitation, Ionic Compound, Solubility, Yield Abstrak: Penelitian ini bertujuan untuk mensintesis dan mengkarakterisasi senyawa ion Barium Sulfat (BaSO?) melalui metode pengendapan serta menganalisis sifat fisik dan kelarutannya berdasarkan hasil eksperimen laboratorium. Sintesis dilakukan dengan mereaksikan larutan Barium Klorida (BaCl?) dan natrium sulfat (Na?SO?) dalam medium berair sehingga terbentuk endapan putih BaSO?. Endapan yang dihasilkan kemudian dipisahkan melalui proses filtrasi, dicuci menggunakan Aquades, dan dikeringkan untuk memperoleh padatan yang stabil. Karakterisasi dilakukan melalui uji fisik dan uji kelarutan. Hasil pengamatan menunjukkan bahwa BaSO? yang diperoleh berbentuk serbuk halus berwarna putih. Pada uji kelarutan, senyawa ini tidak larut dalam air, yang menunjukkan bahwa BaSO? memiliki kelarutan yang sangat rendah. Berdasarkan perhitungan stoikiometri, diperoleh massa teoritis sebesar 2,33 gram, sedangkan massa hasil eksperimen sebesar 0,55 gram, sehingga diperoleh persen rendemen sebesar 23,6%. Nilai rendemen yang relatif rendah menunjukkan bahwa proses sintesis belum berlangsung secara optimal. Secara teoritis, pembentukan endapan BaSO? dipengaruhi oleh nilai hasil kali kelarutan (Ksp) yang sangat kecil, sehingga ion Ba²? dan SO?²? dalam larutan cenderung membentuk fase padat. Hasil penelitian ini menunjukkan kesesuaian dengan teori dari segi pembentukan endapan, sifat fisik, dan kelarutan, meskipun terdapat perbedaan pada hasil kuantitatif yang diperoleh. Kata kunci: BaSO?, Pengendapan, Senyawa Ion, Kelarutan, Rendemen